The Effect of Economic Potential and Social Heterogeneity on Electricity Distribution By Government in Rural Indonesia from 2005-2018 - Triwuli Handayani; Ni Made Sukartini (MediaTrend, 2022)
Indonesia is country that has a plural society. The plural society here is interpretedby the diversity of social identities, namely ethnicity, language, and religion. Thisstudy aims to analyze the effect of diversity of economic potential and the diversityof social identities on acess to electricity distribution provided by the governmentin rural areas of Indonesia. The data source used is secondary data, which areBadan Pusat Statistik (BPS-Statistics Indonesia) data on village potential, namelyPotensi Desa (PODES) in 2005, 2008, 2011, 2014 and 2018. The analysis used ispooled cross section regression. The estimation results using Ordinary Least Square(OLS) found as follows. The OLS estimation found in terms of social diversity, thedistribution of access to electricity outside Java is better than in Java. Meanwhile,based on economic diversity and geographical barriers and accessibility, villages inJava have better access to electricity than Non-Java.